2009
DOI: 10.1007/s11250-009-9368-x
|View full text |Cite
|
Sign up to set email alerts
|

Fertility and viability rates of hydatid cysts in slaughtered animals in the Mazandaran Province, Northern Iran

Abstract: The aim of this study was to determine the fertility and viability of hydatid cysts in slaughtered sheep and cattle. Cysts were collected from the liver and lungs of 169 sheep and 171 cattle infected with Echinococcus granulosus when slaughtered in industrial abattoir in Sari, Iran, 2007-2008. Fertility was determined by the examination of cyst fluid for the presence of protoscoleces. The viability of the protoscoleces was assessed by staining with 0.1% aqueous eosin solution. The fertility rates of hepatic cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
21
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 22 publications
8
21
0
Order By: Relevance
“…The reverse was noticed in pulmonary cysts, where the fertility rate was higher in camels than in sheep because the lung of the camel is a more suitable organ for fertile cyst, as it is known to have a more conducive habitat for the growth of the metacestode [31]. The findings from the present study are supported by those from Libya and Iran [10] [11] [29]. Furthermore, the findings from Iran observed that the hepatic cysts of sheep were more fertile than pulmonary cysts, while other from Jordan found hepatic cysts from sheep were more fertile than those from the camel [27] [32].…”
Section: Fertility and Viability Of Cystic Echinococcosissupporting
confidence: 74%
“…The reverse was noticed in pulmonary cysts, where the fertility rate was higher in camels than in sheep because the lung of the camel is a more suitable organ for fertile cyst, as it is known to have a more conducive habitat for the growth of the metacestode [31]. The findings from the present study are supported by those from Libya and Iran [10] [11] [29]. Furthermore, the findings from Iran observed that the hepatic cysts of sheep were more fertile than pulmonary cysts, while other from Jordan found hepatic cysts from sheep were more fertile than those from the camel [27] [32].…”
Section: Fertility and Viability Of Cystic Echinococcosissupporting
confidence: 74%
“…Recently, Daryani et al (2009) reported that in an abattoir in Sari, Mazandaran Province, the fertility rates of hepatic cyst of sheep and cattle were 47.1 and 1.4%, respectively and the fertility rates of pulmonary cyst of sheep and cattle were 39.4 and 8.1%. In the sheep, the fertility of cysts in the liver was higher than that in lungs, but in the cattle the fertility of cysts in lungs was higher than liver.…”
Section: Discussionmentioning
confidence: 99%
“…Intermediate hosts, as sheep, goats, cattle, camels, buffaloes, pigs, horses and donkeys can be infected by eggs ingestion. The dog-sheep cycle has been reported to be predominant in Southern Europe and Mediterranean Basin [7]. Humans, considered as "dead-end" host, can be accidentally infected acting as intermediate hosts.…”
Section: Introductionmentioning
confidence: 99%